Pengaruh Agresivitas Pajak terhadap Nilai Perusahaan dengan Ukuran Perusahaan Variabel Kontrol pada Sektor Consumer Goods yang Terdaftar di BEI Tahun 2021-2024 - Amri, Salma Usnaini; Elmizan, Gina Havieza (ARZUSIN, 2026)
Tax aggressiveness and firm value have received attention in various studies, yet studies specifically discussing the effect of tax aggressiveness on firm value with company size as a control variable in consumer goods sector companies during the post-COVID-19 pandemic period remain limited. This study aims to analyze the effect of tax aggressiveness on firm value with company size as a control variable in consumer goods sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study used a quantitative approach with an explanatory research design. The research sample consisted of 76 observational data points from consumer goods sector companies selected using purposive sampling based on specific criteria. The data were obtained through documentation of companies’ annual financial reports and analyzed using multiple linear regression with the assistance of SPSS. The results show that tax aggressiveness has a positive and significant effect on firm value, with a calculated t-value of 7.102 and a significance level of 0.000 < 0.05. The regression coefficient of 0.643 indicates that an increase in tax aggressiveness is followed by an increase in firm value. Meanwhile, company size does not have a significant effect on firm value, with a significance value of 0.374 > 0.05. The Adjusted R Square value of 0.394 indicates that tax aggressiveness and company size are able to explain 39.4% of the variation in firm value. These findings contribute to the development of signalling theory and agency theory in explaining the relationship between tax aggressiveness and firm value. The conclusion of this study affirms the importance of corporate tax management strategies in increasing firm value, accompanied by effective tax supervision. The implications of this study include a theoretical contribution to enriching the tax accounting literature and practical implications for companies, investors, and the government in making decisions related to corporate tax policy.